Policies and incentives to promote the transition from degraded pasturelands to sustainable livestock production systems and Livelihoods in the Gutah Hills - Pezo Quevedo, Danilo; Ibrahim, Muhammad Akbar; Nji, Ajaga; Agwe, Jonathan; Azah, Chick Herman (2015)
Centro Agronómico Tropical de Investigación y Enseñanza (CATIE)-MAP